The Plastered Skulls from the Pre-Pottery Neolithic B Site of Yiftahel (Israel) – A Computed Tomography-Based Analysis - Slon, Viviane; Sarig, Rachel; Hershkovitz, Israel; Khalaily, Hamoudi; Milevski, Ianir (PLOS ONE, 2014)
Three plastered skulls, dating to the Pre-Pottery Neolithic B, were found at the site of Yiftahel, in the Lower Galilee (Israel). The skulls underwent refitting and restoration processes, details of which are described herein. All three belong to adults, of which two appear to be males and one appears to be a female. Virtual cross-sections were studied and a density analysis of the plaster was performed using computed tomography scans. These were utilized to yield information regarding the modeling process. Similarities and differences between the Yiftahel and other plastered skulls from the Levant are examined. The possible role of skull plastering within a society undergoing a shift from a hunting-gathering way of life to a food producing strategy is discussed.